Origin of Cancer: Cell work is the Key to Understanding Cancer Initiation and Progression - Hanselmann, Rainer G.; Welter, Cornelius (Frontiers in Cell and Developmental Biology, 2022)
The cell represents the smallest unit of life. It is a structure that maintains order through self-organization. This self-organization is characterized by a high level of dynamism, which is characterized by work. For this work to be done, a continuous high flow of energy is neces-sary. However, the physical relationship between energy and work is not suitable for describ-ing complex biological/medical mechanisms or systems. The many different work processes (work) in human cells are called cell work. They can be grouped into five forms: synthetic, mechanical, electrical cell work, concentration cell work and the generation of heat. In addition to the flow of energy, these cell functions are based on fundamental processes that we summarize with the term Entirety of molecular interaction (EoMI). This is to illustrate that cell work is caused by innumerable molecular reactions and mechanisms. Their number and interactions are so complex that they elude our perception in their entirety. In order to be able to describe cell functions in a biological/medical context, the parameters influencing cell work should be summarized in overarching influencing variables. These are "biological" energy, information, matter and cell mechanics (EMIM). This makes it possible to describe and characterize the cell work involved in cell systems (e.g., respiratory chain, signal transmission, cell structure or inheritance processes) and to demonstrate changes. If the cell work and the different influencing parameters (EMIM influencing variables) are taken as the central property of the cell, specific gene mutations cannot be regarded as the sole cause for the initiation and progression of the cancer disease. This monocausal view does not do justice to the dynamic and highly complex system of a cell. We therefore postulate that each of the EMIM influencing variables described above is capable of changing the cell work and thus the order of a cell in such a way that it can develop into a cancer cell.